El Violin de Ada : la Historia de la Orquesta de Instrumentos Reciclados del Paraguay - Hood, Susan 1954-; Comport, Sally Wern; McConnell, Shelley A. (Nueva York : Simon & Schuster Books for Young Readers, 2016)
The true tale of the Recycled Orchestra of Paraguay, an orchestra made up of children playing instruments built from recycled trash.
Includes bibliographical references.
Keywords: Bordados, Ada Maribel Rios -- Juvenile literature; Orquesta de Instrumentos Reciclados Cateura -- Juvenile literature; Orchestra -- Juvenile literature. -- Paraguay; Orchestral musicians -- Juvenile literature. -- Paraguay